Prenatal ethanol exposure induces susceptibility to premature ovarian insufficiency. Issue 1 (October 2019) - Ni, Yuan; Xu, Dan; Lv, Feng; Wan, Yang; Fan, Guanlan; Zou, Wen; Chen, Yunxi; Pei, Linguo; Yang, Jing; Wang, Hui
Abstract : Prenatal ethanol exposure (PEE) adversely affects the offspring reproductive system. We aimed to confirm the susceptibility to premature ovarian insufficiency (POI) in female PEE offspring and elucidate its intrauterine programming mechanism. The pregnant Wistar female rats were intragastrically administered with 4 g/kg × day of ethanol from gestational day (GD) 9 to 20. Offspring reproductive parameters were detected on GD20, postnatal week (PW) 6 and PW12. The PEE foetuses showed a decreased number of oocytes, increased ovarian cell apoptosis and upregulated expression levels of ovarian insulin-like growth factor 1 (IGF1) signalling pathway and steroidogenic enzymes. The proportion of atretic follicles in adult rats was increased, while the number of anti-Müllerian hormone-positive antral follicles was decreased. The serum oestradiol (E2 ) levels were decreased, but the follicle stimulation hormone levels were elevated. The ovarian Igf1 signalling pathway was transformed from activation during puberty to relative inhibition in adulthood, and the expression levels of ovarian steroidogenic enzymes were inhibited in adulthood. Furthermore, we treated the human granulosa cell line KGN with different ethanol concentrations (15, 30, 60, 120 mM) and found that the expression of IGF1 signalling pathway components, 3β-HSD and P450arom, as well as the production of E2, was increased. After IGF1 siRNA transfection, P450arom expression and E2 production were downregulated. These results suggest that PEE induces POI susceptibility in adult females, which may be caused by over-activation of the foetal ovarian Igf1 signalling pathway and steroidogenesis under PEE, resulting in accelerated early development of folliculogenesis and depletion of primordial follicles.